2010
DOI: 10.1177/1076029609360528
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Venous Thromboembolism With Inflammatory Bowel Disease

Abstract: The purpose of this study is to determine the incidence of venous thromboembolism (VTE) in patients with ulcerative colitis and patients with Crohn disease. The number of patients discharged from hospitals throughout the United States with a diagnostic code for ulcerative colitis and for Crohn disease from 1979 through 2005 was obtained from the National Hospital Discharge Survey. The incidence of VTE among medical patients with ulcerative colitis was 21 000 of 1 129 000 (1.85%) and among medical patients who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 16 publications
2
25
0
1
Order By: Relevance
“…reported that the incidence of venous thromboembolism among the CD patients discharged from hospitals throughout the United States was 1.22%. [40] Similarly, we found a significant association between the severity of the disease and the frequency of DVT in our patients, which is consistent with that reported in the literature. [41]…”
Section: Discussionsupporting
confidence: 92%
“…reported that the incidence of venous thromboembolism among the CD patients discharged from hospitals throughout the United States was 1.22%. [40] Similarly, we found a significant association between the severity of the disease and the frequency of DVT in our patients, which is consistent with that reported in the literature. [41]…”
Section: Discussionsupporting
confidence: 92%
“…The possible association between IBD and VTE was first reported in 1936 by Bargen and Barker, who described 18 patients with thromboembolic disease (predominantly venous) from among more than 1000 patients treated for IBD at the Mayo Clinic . Since that time, several recent publications have suggested that patients with IBD have an increased risk of VTE, although some heterogeneity can be seen in the literature . For example, while Nguyen et al .…”
Section: Introductionmentioning
confidence: 99%
“…In population based cohort studies, patients with IBD have a 1.5–3 fold increase in risk of venous thromboembolism 1, 2, 8, 9 . Furthermore, VTE in such patients is associated with considerable morbidity and mortality with higher rates of death from pulmonary embolism in IBD patients than the general population 5, 10 .…”
Section: Introductionmentioning
confidence: 99%